Analisis Perbandingan Kebangkrutan dengan Metode Altman Z-Score, Springate, dan Zmijewski - Ukhti Apse Raviani; Yanuar Ramadhan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The research was conducted to find out how much potential the company's bankruptcy is during this pandemic. Bankruptcy prediction is done by using Altman Z-Score, Springate, and Zmijewski methods. The study used a different test, namely the Kruskal-Wallis H Test. The companies used in this study were the hotel, restaurant, and tourism sub-sector companies listed on the Indonesia Stock Exchange. The research sample uses 16 hotel, restaurant, and tourism sub-sector companiesilisted on the Indonesia Stock Exchange for the 2016-2020 periods. Sample selection using a purposive sampling technique. From the hypothesis test conducted, the results show that there are differences between the Altman Z-Score, Springate, and Zmijewski prediction methods in predicting bankruptcy. In this study, the Zmijewski method is the most accurate prediction model with an accuracy rate of 98% with the results of 2 companies experiencing bankruptcy. Next is the Altman ZScore method with an accuracy rate of 61% with the results of 8 companies experiencing bankruptcy and the Springateimethod withianiaccuracyirate of 30% with the results of 11 companies experiencing bankruptcy.